An efficient and mild access to N-acetyl protected purine nucleosides based on a chemoselective enzymatic hydrolysis - Palacio, Cyntia M.; Sabaini, María Belén; Iribarren, Adolfo Marcelo; Iglesias, Luis Emilio (Journal of Biotechnology)
N-Monoacetylated derivatives of ribo- (adenosine, guanosine) and 2′-deoxyribonucleosides (2′-deoxyadenosine and 2′-deoxyguanosine), useful as oligonucleotide building blocks, were obtained in 88–100% by enzymatic chemoselective hydrolysis of the corresponding peracetylated nucleosides. Among the tested hydrolases, most satisfactory results were found with acylase I from Aspergillus melleus and Candida antarctica lipase B. For acylase I, the observed chemoselectivity towards ester hydrolysis, without amide reaction, broadens the information about the selectivity of the enzyme and its synthetic applications in the field of nucleosides. Fil: Palacio, Cyntia M. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina Fil: Sabaini, María Belén. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Iribarren, Adolfo Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y Biología Molecular "Dr. Héctor N. Torres"; Argentina. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina Fil: Iglesias, Luis Emilio. Universidad Nacional de Quilmes. Departamento de Ciencia y Tecnología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina